The role of various collagen types in tumor biology: a review - Zhou, Yuchuan; Jiang, Zhonghui; Cao, Lu; Yang, Jianquan (Frontiers in Oncology, 2025)
Collagen comprises approximately 30% of the body’s protein content and is essential for maintaining the structural integrity, support, and strength of the skin, muscles, bones, and connective tissues. Recent research has further elucidated its role in various aspects of tumor biology, including tumorigenesis, invasion, migration, drug resistance, and recurrence. Furthermore, collagen is involved in prognostic assessments, the evaluation of therapeutic efficacy, immunoregulation, and the identification of potential treatment targets in oncology. This review examines a range of tumor types, including lung, gastric, breast, melanoma, and colorectal cancers, among others. Our objective is to differentiate these tumors based on the specific types of collagen present and to analyze the roles of various collagen types in tumor development, progression, prognosis, and their potential as therapeutic targets.